Junior Wonder Camp / Frederica Freadrick ... [et al.] - Freadrick, Frederica; jelius, Jevella Myrna; Moligan, Eudrer T.; Francis, Elka Vionna Lissa; Hasli, Noorhayati (2016)
Jr. Wondercamp (Junior Wondercamp) will be operating in Kundasang, Ranau, Sabah and is expected to be open to the public on January 2017. Our goal is to promote a sense of belonging to a large freethought community, encourage critical thinking, promote respect for others who hold different viewpoints, and provide a safe and fun environment for personal and social development and most importantly to have fun.